Analysis of Circular Economy Models in the Textile Industry: International Experiences and Practices in Vietnam - Ngọc Anh, Le Thi; Van Linh, Nguyen; Nam, Nguyen Hoang; Dieu Dieu Ngoc, Nguyen; Ngoc Ha, Vo; Huy Manh, Nguyen (VNU Journal of Science: Policy and Management Studies; Vol 41 No 1DO - 10.25073/2588-1116/vnupam.4528, 2025)
In line with the global trend, Vietnam’s textile industry is gradually transitioning with an increasing number of circular economy models. This article conducts a study of international experiences and compares them with the current practices in Vietnam. It provides a detailed analysis using a five-stage circular economy framework and focuses on two main aspects: specific circular economy models within the textile sector, and government policies that enable the development of these models. The research findings highlight key weaknesses, such as the fragmented and small-scale nature of circular models in Vietnam compared to international practices, a strong focus on waste treatment to meet environmental standards rather than adopting a holistic circular economy approach across the entire value chain, and limitations due to the lack of detailed policies and guidelines for circular economy models in the textile sector. Based on these findings, the article proposes specific recommendations on perspectives to adopt, models that Vietnam can learn from, and necessary policy conditions for policymakers to consider.